2006
DOI: 10.1021/ma060809h
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Polyurethane/POSS Hybrid Aqueous Dispersions Prepared by Homogeneous Solution Polymerization

Abstract: Aqueous polyurethane dispersions were prepared with 4−10 wt % of functionalized polyhedral oligomeric silsesquioxanes (POSS) via homogeneous solution polymerization in acetone followed by solvent exchange with water. The use of acetone as the initial polymerization solvent allowed for the facile incorporation of both diamino and dihydroxy functional POSS monomers in a homogeneous reaction environment. After addition of water and removal of the acetone, stable dispersions with unimodal particle sizes were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 40 publications
10
99
0
Order By: Relevance
“…These findings are consistent with previously reported studies showing increased surface hydrophobicity for other POSS/polymer systems and POSS molecules with fluorinated alkyl chains attached to the POSS cage. 12,[21][22][23][24] Surface dynamics were further studied via dynamic water contact angle analysis. The advancing (h a ) and receding (h r ) water contact angles were measured and their difference, the contact angle hysteresis (h h ), was calculated (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with previously reported studies showing increased surface hydrophobicity for other POSS/polymer systems and POSS molecules with fluorinated alkyl chains attached to the POSS cage. 12,[21][22][23][24] Surface dynamics were further studied via dynamic water contact angle analysis. The advancing (h a ) and receding (h r ) water contact angles were measured and their difference, the contact angle hysteresis (h h ), was calculated (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…In general, hybridization of an organic polymer matrix with inorganic POSS results in improved thermal and mechanical properties along with increase in oxidative and flame resistance. [3][4][5][6][7][8]11 Recently Nanda et al 12 synthesized well dispersed polyurethane/POSS hybrid materials utilizing a solution polymerization process. Ordered morphologies with homogenously distributed POSS domains ($100-150 nm) were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Using the acetone method with 3-(2-aminoethyl) amino propyl-heptaisobutyl-POSS (diamino-POSS), 2,3-propanediol propoxy-heptaisobutyl-POSS (diol-POSS), and other raw materials, Nanda et al 40 synthesized POSS/PU hybrid dispersions, according to the synthesis steps shown in Figure 4. All the PU-POSS dispersions studied were stable for more than 6 months.…”
Section: Amino-possmentioning
confidence: 99%
“…As with other polymer systems, many of the POSS hybrids do yield elastomeric PU with improvements in physical and thermal properties at relatively low levels of POSS incorporation. The waterborne PU hybrid dispersions were synthesized by incorporating amino-and hydroxyl-terminated POSS macromers into the PU ionomeric backbones, using a homogeneous solution polymerization, followed by a solvent exchange with water (i.e., the "acetone process") (Nanda & Wicks 2006). The absence of crystalline domains evidenced the incorporation of POSS macromer in the PU hard segments.…”
Section: Modification Of Polyurethanes and Polyureas By Cfpsmentioning
confidence: 99%